THE IMPACT OF WORKPLACE DEMOCRACY ON THE PROACTIVE BEHAVIOUR OF EMPLOYEES - Jinan Shihab Ahmed, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2022)
Proactive employee behaviour provides immense benefits to organisations at both macro and micro levels of analysis. Studies have suggested workplace democracy one of its significant antecedents. However, research on the workplace democracy–proactive employee behaviour relationship has been grossly neglected. The current study employed the proactive behaviour theory to address the general association between workplace democracy and proactive employee behaviour in Iraqi higher educational institutions, based on assessments of the constructs at the global level of analysis. Scoping review was used in sourcing relevant literature upon which the hypothesis was developed. In testing the hypothesis, data were collected from a sample of 244 faculty (Ffemale, 29.02%; Mmale, 70.98%) drawn from Al-Qadisiyah University, using validated measures of workplace democracy (α = 0.915) and proactive behaviour (α = 0.787). PLS-SEM in SmartPLS was used in the analysis and test of the hypothesis. The results confirm that workplace democracy significantly and positively impacts the proactive behaviours of employees at the Al-Qadisiyah University (β = 0.011, t = 2.799, p = 0.005). Based on the discussion of the results, several recommendations were proffered.